The fall of the city of Ur And the end of the modern Sumerian era in ancient Iraq A study in the light of archaeological data (Journal of the College of Basic Education, 2022)
The city of Ur is one of the most famous civilized cities in Mesopotamia, and it is known locally as (Tal al-Muqir), like many archaeological sites in ancient Iraq. Its remains are located today, 365 km southeast of Baghdad, and 15 km southwest of the city of Nasiriyah.1Ur is located in ancient times near the Euphrates River, as it was used as a commercial outlet for importing and exporting goods, as well as irrigating lands and orchards. ), and may have arisen over the remains of a village from this roleThe city of Ur, since its inception, passed through the successive roles of civilization, and was a religious center